A uterus didelphys with breech presentation in a previously scarred uterus; an incidental finding - B., Shilpa H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A didelphic uterus results from failed fusion of the paired mullerian ducts characterized by two separated uterine horns, each with an endometrial cavity and uterine cervix. Pregnancies develop in one of the two horns, and of the major uterine malformations, the didelphys uterus has the best reproductive prognosis. Improved fetal survival may be secondary to earlier diagnosis, which favors earlier and more intensive prenatal care. Pregnancy is associated with an increased risk of malpresentations and premature labor, although many patients will have no reproductive difficulties. We report a case of successful pregnancy outcome in our institute in a case of didelphys uterus by Caesarean section.